Geochemical Evidence of the Lateritic Bauxite Deposits in the Sucullu-Yalvac Region (NE Isparta Angle, Southwestern Turkiye) with Emphasis on a Basic Source - Cengiz, Oya; Aydogan, M. Selman; Onal, Betul Coskun (Springer Heidelberg, 2025)
The Sucullu (Yalvac-Isparta, SW Turkiye) lateritic bauxite horizon lies directly on the alkali basaltic lavas (e.g. doleritic basalt) occurring on the carbonate platform of Jurassic age. This horizon is associated with thickness in the range of 5-30 m (average of 15 m) in the NW-SE direction. Lateritic bauxite occurrences have dominant mineral assemblages of clay (kaolinite, smectite), Fe-oxy-hydroxides (hematite, goethite), Al-rich minerals (boehmite, gibbsite), feldspar, cristobalite, anatase, quartz, calcite and dolomite. From bottom to top, lateritic profile is divided into 4 zones as (1) weathered basaltic rock, (2) clayey laterite zone, (3) ferrigenous laterite zone, (4) bauxite zone. Geochemically, lateritic bauxites have average values of 26.04 wt% Al2O3, 19.77 wt% Fe2O3 and 29.48 wt% SiO2. Chemical analyses of whole rock samples and the mineral assemblage suggest that coexisting minerals of lateritic bauxite are highly aluminous and ferrigenous. Laterite and bauxite zones are typical with weak-to-moderate lateritisation. High CIA values (similar to 85.7), IOL values (up to 89.62), strong depletion of major elements (Si, Mg, Ca, Na, K) and concentration of immobile elements such as Ti, Cr, Zr, Ga and REEs reflect that the studied samples can be classified as lateritic bauxite, and formed through intense chemical weathering of alkali basalt parent rocks, similar to the Payas and Cariksaraylar bauxites in southern Taurides (Turkiye), and in the Darai-Daldali region of India. In respect of tectonic setting, these lateritic bauxites occurred under hot-humid tropical climate dominated during upper Cretaceous. Afterwards, formed lateritic bauxite materials were transported into the sea on dolomitic limestones with erosion from a terrestrial environment, and thin-bedded dolomitic limestones were deposited again on these transported laterites in the marine environment.
Keywords: Lateritic bauxite; Clay; Alkali basalt; Sucullu; Tauride; Turkiye